Emerging Technologies in Hydraulic Fracturing and Gas Flow Modelling - Imo-Imo Israel Eshiet, Kenneth; Moghanloo, Rouzbeh G. (IntechOpen, 2022)
Emerging Technologies in Hydraulic Fracturing and Gas Flow Modelling features the latest strategies for exploiting depleted and unconventional petroleum rock formations as well as simulating associated gas flow mechanisms. The book covers a broad range of multivarious stimulation methods currently applied in practice. It introduces new stimulation techniques including a comprehensive description of interactions between formation/hydraulic fracturing fluids and the host rock material. It provides further insight into practices aimed at advancing the operation of hydrocarbon reservoirs and can be used either as a standalone resource or in combination with other related literature. The book can serve as a propaedeutic resource and is appropriate for those seeking rudimentary information on the exploitation of ultra-impermeable oil and gas reservoirs. Professionals and researchers in the field of petroleum, civil, oil and gas, geotechnical and geological engineering who are interested in the production of unconventional petroleum resources as well as students undertaking studies in similar subject areas will find this to be an instructional reference.